Formation of Linear Programming Models of Water Price Compliant to the Regulation of Ministry of Home Affairs, Indonesia - Hek, Tan Kim; Hou, Amin (Universitas Muhammadiyah Mataram, 2025)
Regional Drinking Water Company (PDAM) Tirtanadi manages Medan City's clean water. PDAM divides its clients into seven categories, with Group I being low-income areas that require water subsidies. PDAM does not yet have a mathematical model for water rates, but it depends on Minister of Home Affairs Regulation No. 23, which gives legal guidance. Since there is no mathematical model, this research uses linear programming (LP) to establish each group's minimal water tariff. PDAM bases its water pricing on the Minister of Home Affairs Regulation No. 23 of 2006 and uses the LP model. The LP model reduces complicated computations into linear equations, making them easier to comprehend and apply. The computed water rates match PDAM pricing for six consumer categories, according to the research. One group, Group II Block I, has a higher tariff ratio of 2.3:1. Model parameters are more susceptible to changes in costs, consumption volume, and payment capability of this group, causing this disparity. This study's new goal is to minimize high-water-use clients. Other groupings remained unchanged. LP models establish PDAM's minimum water rates and optimize water tariff calculation effectively and equitably using analytical methods. PDAM may utilize the LP model to determine pricing that cover all expenditures, but Minister of Home Affairs Regulation No. 23 of 2006 continues to keep tariffs cheap and not a social burden on Medan. This research suggests that additional monopolistic enterprises and other water resource management for 37 Indonesian provinces may utilize its minimum water selling price approach. In the mathematical equation, the LP model is correct. Thus, PDAM Tirtanadi may use it to calculate the minimal water selling price by considering economic considerations. Water firms must help PDAM researchers who are willing to supply data, including polite service from each division's workers.